Sleep duration and life satisfaction - Alan T. Piper (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Sleep is an important part of life, with an individual spending an estimated 32 years of her life asleep. Despite this importance, little is known about life satisfaction and sleep duration. Using German panel data, it is shown that sleep is an important factor for life satisfaction and that maximal life satisfaction is associated with about eight hours of sleep on a typical weekday. This figure represents, on average, an hour more than people currently sleep suggesting that more sleep would lead to a higher reported satisfaction with life.
Keywords: C23; D10; I31; 330; sleep; life satisfaction; SOEP; fixed effects